Estudio de factibilidad para la prestación de servicios complementarios en unidades residenciales en el municipio de Jamundi Valle del Cauca. (2020)
This feasibility study has the purpose of evaluating the possibility of creating a company that provides cleaning services in residential units in the municipality of Jamundi, taking advantage of the increase in the real estate sector in this region.